Optimization of Ultrasound-Assisted Extraction of Polysaccharides from Mulberry Leaves by Response Surface Methodology - Fang, Miaoli; Yan, Wei; Chen, Keke; Ying, Zhi; Han, Xiaoxiang (Asian Journal of Chemistry, 2014)
Response surface methodology was applied to optimize the ultrasound-assisted extraction of polysaccharides from mulberry leaves. A central-composite rotatory design (CCRD) was used for experimental design and analysis of the results to obtain the optimum extraction conditions. Based on the response surface methodology analysis, optimum conditions were: ratio of water to raw material 15:1, power of ultrasound 60 W, extraction temperature 80 °C and extraction time 20 min. Under the optimized conditions, the experimental values were in close agreement with values predicted by the mathematical model. Compared with conventional solvent extraction, ultrasound-assisted extraction was a better method to extract polysaccharides. The crude polysaccharides prepared under optimum conditions contained 55.06 % total sugar, 14.02 % protein, 14.49 % moisture and 17.48 % ash.